Considerations for Phage Therapy Against Mycobacterium abscessus - Senhaji-Kacha, Abrar; Esteban, Jaime; Garcia-Quintanilla, Meritxell (Frontiers in Microbiology, 2021)
There is a global increasing number of M. abscessus infections, especially pulmonary infections. Reduced therapeutic options exist against this opportunistic pathogen due to its high intrinsic and acquired levels of antibiotic resistance. Phage therapy is a promising afresh therapy which uses viruses to lyse bacteria responsible for the infection. Bacteriophages have been recently administered under compassionate use to a 15-year-old patient infected with M. abscessus in combination with antibiotics with excellent results. This minireview highlights different recommendations for future phage administrations such as where to look for new phages, the use of cocktail of mycobacteriophages to broaden phage specificity and to tackle resistance and phage insensitivity due to temperate phages present in bacterial genomes, the combined use of phages and antibiotics to obtain a synergistic effect, the liposomal administration to reach a prolonged effect, intracellular delivery and protection against neutralizing antibodies, and the convenience of using this strategy in patients suffering from cystic fibrosis since phages are believed to promote immunomodulatory actions and eliminate biofilms.